(untitled) (Web of Teachers: Inderscience Research, 2024)
This article discusses about the key features of the given novel by Louisa May. Detailed analysis of the protagonist women characters tried to give in this article. While discussing the writer’s artistic skill of creating several characters we tried to refer to some researches done by scholars of the international values.